And Then There Were Three…: Extreme Regeneration Ability of the Solitary Chordate Polycarpa mytiligera - Gordon, Tal; Upadhyay, Arnav Kumar; Manni, Lucia; Huchon, Dorothée; Shenkar, Noa (Frontiers in Cell and Developmental Biology, 2021)
Extensive regenerative ability is a common trait of animals capable of asexual development. The current study reveals the extraordinary regeneration abilities of the solitary ascidian Polycarpa mytiligera. Dissection of a single individual into separate fragments along two body axes resulted in the complete regeneration of each fragment into an independent, functional individual. The ability of a solitary ascidian, incapable of asexual development, to achieve bidirectional regeneration and fully regenerate all body structures and organs is described here for the first time. Amputation initiated cell proliferation in proximity to the amputation line. Phylogenetic analysis demonstrated the close affinity of P. mytiligera to colonial species. This evolutionary proximity suggests the ability for regeneration as an exaptation feature for colonial lifestyle. P. mytiligera’s exceptional regenerative abilities and phylogenetic position highlight its potential to serve as a new comparative system for studies seeking to uncover the evolution of regeneration and coloniality among the chordates.